Cisto dentígero: modalidades de tratamento - Caliento, Rubens [UNESP]; Mannarino, Francesco Salvatore [UNESP]; Vieira, Eduardo Hochuli [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
INTRODUCTION: The dentigerous cyst is the second most common odontogenic cyst in the jaws. It is a benign lesion of odontogenic epithelium derived from the crown of a tooth that has not erupted, but of uncertain etiology. They are generally radiolucent and usually unilocular. These lesions are observed in routine examinations or when the eruption of a permanent tooth is delayed. The third molars and maxillary canines are the most affected teeth, and also the high occurrence of this lesion is associated with supernumerary teeth and odontomas. The dentigerous cyst occurs mainly in the first three decades of life, It's growth is slow, asymptomatic and can reach considerable size causing facial deformity, displacement and impaction of teeth and/or surrounding structures. OBJECTIVE: Definition of marsupialization and enucleation techniques as well as consideration of important objective criteria for the treatment plan like cyst size, age, proximity to anatomical structures and clinical importance of the involved tooth. Despite the clinical peculiarities of each case and the chosen treatment method, the prognosis of these lesions are favorable when appropriate therapy is used. MATERIAL AND METHOD: This study will present a case report treated by maneuver of decompression followed by enucleation and discussion of treatment modalities. RESULT: The patient is on two years of postoperative without signs of relapse and absence of paresthesias in the face. CONCLUSION: The technique preserved the neurosensory function and was effective for the extinction of the lesion.

INTRODUÇÃO: O cisto dentígero é o segundo cisto odontogênico mais frequente nos maxilares. É uma lesão benigna, derivada do epitélio odontogênico da coroa de um dente não erupcionado, porém de etiopatogenia incerta. São geralmente radiotransparentes e, mais comumente, uniloculares. Estas lesões são observadas em exames de rotina ou quando não ocorre o irrompimento de um dente permanente. Os terceiros molares inferiores e os caninos superiores são os dentes mais acometidos, sendo também alta a ocorrência desta lesão em dentes supranumerários e associados a odontomas. O cisto dentígero ocorre principalmente nas três primeiras décadas de vida, tendo um crescimento lento e assintomático; pode atingir dimensões consideráveis, causando deformidade facial, impactação e deslocamento de dentes e/ou estruturas adjacentes. OBJETIVO: Definição das técnicas de marsupialização e enucleação, bem como consideração de critérios objetivos importantes para o plano de tratamento, como tamanho do cisto, idade, proximidade com estruturas anatômicas e importância clínica do dente envolvido. Apesar das peculiaridades clínicas de cada caso e do método de tratamento escolhido, o prognóstico destas lesões é favorável, quando se emprega apropriada terapêutica. MATERIAL E MÉTODO: O presente estudo apresentará um relato de caso tratado através da manobra de descompressão seguida de enucleação, bem como uma discussão acerca das modalidades de tratamento. RESULTADO: O paciente encontra-se em pós-operatório de dois anos sem sinais de recidiva da lesão e ausência de parestesias em face. CONCLUSÃO: A técnica empregada preservou a função neurossensorial e mostrou-se eficiente para a cura da lesão.
Dentigerous cyst: modalities of treatment
Keywords: Cystic decompression; dentigerous cyst; odontogenic cysts; Descompressão cística; cisto dentígero; cistos odontogênicos